The Effect of Low-Temperature Thermal Pre-Treatment on Methane Yield of Pig Manure Fractions - Sutaryo, Sutaryo; Ward, Alastair James; MÃ¸ller, Henrik Bjarne (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The aim of the present study was to evaluate the effect of low-temperature thermal pre-treatment on the methane yield of pig manure fractions. Four different temperatures ranging from 65°C to 80°C were applied for 20 h to whole pig manure and the solid fraction of pig manure derived from solid-liquid manure separation. The results showed significant improvements in methane yield both in pig manure and solid-fraction pig manure at 11 d of the batch digestion test. The improvement was between 9.5-22.5% for pig manure and 6.1-25.3% for solid fraction pig manure. However, at 90 d of the batch digestion assay the effect of low-temperature pre-treatment on methane yield was significant only for the 65°C treatment. Application of low-temperature thermal pre-treatment appears to be a promising method to improve methane yield of pig manure fractions, particularly when surplus thermal energy is available. Key words: biogas, anaerobic digestion, thermal pre-treatment, pig manure, methane. Abstrak. Penelitan ini bertujuan untuk mengevaluasi pengaruh pre-treatment pada suhu rendah terhadap produksi methan dari bagian manure babi. Perlakuan pre-treatment yang digunakan berupa empat level temperatur mulai dari 65°C sampai dengan 80°C selama 20 jam yang diterapkan pada manure babi dan bagian padat manure babi yang diperoleh dari pemisahan bagian cair dan bagian padat manure babi. Hasil penelitian menunjukkan adanya peningkatan produksi methan secara signifikan setelah 11 hari inkubasi dengan digester model batch. Produksi methane meningkat antara 9,5-22,5% pada manure babi dan 6,1-25,3% pada bagian padat manure babi. Namun demikian setelah 90 hari inkubasi, pengaruh dari penggunaan pre-treatment pada suhu rendah hanya berpengaruh siginifikan pada temperatur 65°C saja. Penggunaan pre-treatment pada suhu rendah menunjukkan bahwa metode tersebut merupakan metode yang menjanjikan untuk meningkatkan produksi methan dari manure babi khususnya apabila terdapat surplus energi. Kata kunci : biogas, digesti secara anaerob, pre-treatment dengan pemanasan, manure babi, methan